Winning moves - Park, Louise 1961-; Matthews, Melanie 1986-; May, Kyla (North Mankato, Minnesota Picture Window Books, a Capstone imprint, 2015)
Ten-year-old Star Girl, Adelaide Banks, of the Space Education and Action School, and her friend Miya, Astron Girl, are sent on a mission to the planet Aquare, where the underwater life forms are being poisoned by a purple goo--they must find the source and somehow stop it, even though the substance dissolves their special survival suits
"First published in 2011 by Macmillan Education Australia Pty Ltd."
English stories
007-010
GRL: O
1 2 13 15
NEW_ZTN_GN
Keywords: Adventure stories; Boarding schools -- Juvenile fiction; Environmental disasters -- Juvenile fiction; Life on other planets -- Juvenile fiction; Marine pollution -- Juvenile fiction; Adventure and adventurers -- Fiction; Boarding schools -- Fiction; Environmental disasters -- Fiction; Life on other planets -- Fiction; Marine pollution -- Fiction; Schools -- Fiction; Science fiction; Adventure fiction; Science fiction